Identification and characterization of small RNAs in the hyperthermophilic archaeon Sulfolobus solfataricus. - Ning Xu; Yan Li; Ying-Tao Zhao; Li Guo; Yuan-Yuan Fang; Jian-Hua Zhao; Xiu-Jie Wang; Li Huang; Hui-Shan Guo (PLoS ONE, 2012)
The term RNA silencing (RNA interference, RNAi) describes a set of mechanisms that regulate gene expression in eukaryotes. Small interfering RNAs (siRNA) and microRNAs (miRNAs) are two major types of RNAi-associated small RNAs (smRNAs) found in most eukaryotic organisms. Despite the presence of a plethora of non-coding RNAs longer than 50-nucleotide (nt) in length in various species of Archaea, little is known about smRNAs in archaea that resemble the 20-24-nt long smRNAs found in eukaryotes, which have been implicated in the post-transcriptional control of gene expression. Here, we report the finding of a large number of smRNAs approximatelly 20-nt in length, including phased smRNAs and potential miRNAs, from the hyperthermophilic archaeon Sulfolobus solfataricus p2 (Ssp2) based on deep sequencing. The expression of some of the miRNA candidates in Ssp2 was confirmed. Consistent with the Ssp2 hyperthermophilic properties, we found that higher temperatures more efficiently induced the production of the miRNA candidates in an in vitro system using the putative foldback precursor transcripts incubated with Ssp2 extract. Although we initially predicted putative target genes of some miRNA candidates, further analysis mapped the cleavage sites downstream of the miRNA candidate complementary regions, similar to those involved in plant miRNA-mediated TAS transcript cleavage. We also identified smRNAs from clustered, regularly interspaced, short palindromic repeat (CRISPR) loci, which play important roles in prokaryotic microbial defense systems. Archaea represent a unique life form next to Bacteria and Eukarya, and our results may provide a useful resource for further in-depth study on the regulation and evolution of smRNAs in this special organism.